COVID-19, INFODEMIC AND CYBER SECURITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Thе present article tries to trace the impact of some processes related to the COVID-19 pandemic on some areas of public life and in particular on national security. The analysis focuses on two main points, namely the infodemic and cybersecurity, as during COVID-19 they stood out as problems that will continue over time. The COVID-19 pandemic has been a challenge that requires the international community, governments and political elites to address multiple dimensions that go beyond just the effects on population health and also have an impact on security aspects. The starting point of the analysis is, of course, the social determinants of the right to health, which promote public health as an element of security and at the same time as one of the goals of sustainable development. In fact, it is precisely some of the determinants of the right to health that are subject to the infodemic, false or misleading information deliberately created to harm a person, social group, organization or country. Furthermore, the weaknesses the pandemic has so far highlighted point to an urgent need for a stronger international framework that would counteract the spread of misinformation and increasing complexity of cyberattacks. That calls for an all-rounded strategy that includes increased international cooperation, public awareness, and the application of cutting-edge technical solutions. An appropriate methodology has been used in view of the delicate matter of health, which becomes even more vulnerable when subjected to infodemic or cybercrime. The main conclusion of the authors is that, in addition to improving international legislation with a view to preparing for and preventing future pandemics, more attention should also be paid to the phenomena that accompany them, such as the infodemic and cybercrime. This is of utmost importance, as they could be expected to develop on a much larger scale in possible future pandemics. The international community and national elites should discuss and take measures to deal with these phenomena.